Dynamic Bayesian Cluster Analysis of Live‐Cell Single Molecule Localization Microscopy Datasets. Issue 9 (3rd June 2018) - Griffié, Juliette; Burn, Garth L.; Williamson, David J.; Peters, Ruby; Rubin‐Delanchy, Patrick; Owen, Dylan M.
Abstract: Until recently, single‐molecule localization microscopy (SMLM) was constrained to the study of fixed cells, limiting analysis to the structural characterization of cell anatomy. The extension of SMLM to live‐cell imaging enables the dynamic visualization of molecular organization, paving the way for more functional studies. If associated with novel quantification tools such as presented here, it has the potential to provide a unique insight into cellular machinery at the nanoscale. While cluster analysis for conventional SMLM data sets is relatively well established, the extension of SMLM to live‐cell imaging lacks the required analytical tools. Here, a Bayesian‐based cluster analysis strategy is presented for live‐cell SMLM that allows the dynamics of nanoscale molecular clusters to be analyzed for the first time, generating functional information otherwise lost in fixed cell studies. The method is validated on simulations as well as on experimental data sets derived from naive CD4 + T‐cell synapses. Abstract : When associated with dedicated analysis tools, live‐cell single‐molecule localization microscopy (SMLM) provides quantification of dynamic nanoscale cellular processes, uniquely bridging the gap between structural and functional studies. A novel framework is provided for the quantification of protein cluster dynamics in live‐cell SMLM data, and is demonstrated via simulation and experimental data from primary human naive T‐cells.